2016
DOI: 10.5335/rfo.v21i2.6103
|View full text |Cite
|
Sign up to set email alerts
|

Estudo in vitro sobre a efetividade de desinfetantes na limpeza de cones de guta-percha

Abstract: Introdução: para se obter um tratamento endodôntico de sucesso, várias etapas devem ser seguidas. Igual-mente, um rigoroso esquema para máxima redução dos microrganismos presentes deve ser seguido bem como para sua não introdução. O material obturador de canais mais utilizado mundialmente, a guta-percha, por não poder ser esterilizada, deve ser desinfetada para que não haja a recontaminação do conduto radicular. Objetivo: avaliar a capacidade biocida de três soluções: hipoclorito de sódio a 5,25%, clorexidina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…In the present work, the tests performed with 2% chlorhexidine also indicated satisfactory decontamination within 15 seconds in all tested cones. Such findings are contrary to those found in the literature, whose results showed disinfection only within one minute 18,20 . However, some authors have shown that the time of 30 seconds is sufficient 21 , while other studies have shown that 2% chlorhexidine is only effective within 10 minutes 14 .…”
Section: Discussioncontrasting
confidence: 99%
“…In the present work, the tests performed with 2% chlorhexidine also indicated satisfactory decontamination within 15 seconds in all tested cones. Such findings are contrary to those found in the literature, whose results showed disinfection only within one minute 18,20 . However, some authors have shown that the time of 30 seconds is sufficient 21 , while other studies have shown that 2% chlorhexidine is only effective within 10 minutes 14 .…”
Section: Discussioncontrasting
confidence: 99%